Association between hemoglobin glycation index and poor outcome after endovascular thrombectomy in acute ischemic stroke - Yang, Yan; Liu, Mei; Huang, Shungui; Zhu, Chen; Li, Guangzong; Wang, Bin; Luo, Xiaojing; Zhang, Lingwen; Song, Weizheng (Frontiers in Aging Neuroscience, 2025)
BackgroundThe prognostic significance of hemoglobin glycation index (HGI) on acute ischemic stroke (AIS) patients treated with endovascular thrombectomy (EVT) remained unclear. This study aimed to investigate the association between HGI and the risk of poor outcome after EVT.MethodsWe retrospectively enrolled AIS patients with large vessel occlusion in the anterior circulation treated with EVT from a multicenter study. Poor outcome was defined as a modified Rankin scale score > 2 points at 90 days after EVT. We used multivariable logistic regression models to investigate the association between HGI and poor outcome. We employed the restricted cubic spline curve to visualize the association between HGI and the risk of poor outcome after EVT.ResultsAmong the 403 enrolled patients (median age, 72 years; 63.8% male), a total of 198 (49.1%) patients had poor outcome at 90 days. The restricted cubic spline curve showed that there was a U-shape relationship between HGI and the risk of poor outcome (P for non-linearity < 0.001). After divided patients into three groups based on HGI tertiles, HGI (tertile 1 vs. 2) was significantly associated with poor outcome [odds ratio (OR), 3.84; 95% confidence interval (CI), 2.08–7.22; P < 0.001] and early neurological deterioration (OR, 3.11; 95% CI, 1.55–6.44; P = 0.002) in multivariable analyses. Adding HGI into models improved the discriminative ability for poor outcome (P < 0.001).ConclusionIn conclusion, our study identified a U-shaped relationship between HGI and poor outcome, with low HGI levels significantly associated with poor outcome after EVT.